2010
DOI: 10.4103/1319-3767.65183
|View full text |Cite
|
Sign up to set email alerts
|

Functional bowel disorders in Iranian population using Rome III criteria

Abstract: Background/Aim:To study the prevalence and risk factors of functional bowel disorders (FBD) in Iranian community using Rome III criteria.Materials and Methods:This study was a cross-sectional household survey conducted from May 2006 to December 2007 in Tehran province, Iran, including 18,180 participants who were selected randomly and interviewed face-to-face by a validated questionnaire based on Rome III criteria.Results:In all, 1.1% met the Rome III criteria for irritable bowel syndrome (IBS), 2.4% for funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 10 publications
4
37
0
1
Order By: Relevance
“…According to the Rome criteria, the primary difference in symptoms between functional diarrhea and IBS-D is that abdominal pain must be present in the latter. A study in Iran using Rome III, reported that some symptoms were more frequent in IBS-D than functional diarrhea [6]. In our study, IBS-D also had more frequency of the diarrhea symptoms, such as more than three bowel movements a day, having to rush to the toilet to have a bowel movement, feeling of incomplete emptying after a bowel movement, and so on.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…According to the Rome criteria, the primary difference in symptoms between functional diarrhea and IBS-D is that abdominal pain must be present in the latter. A study in Iran using Rome III, reported that some symptoms were more frequent in IBS-D than functional diarrhea [6]. In our study, IBS-D also had more frequency of the diarrhea symptoms, such as more than three bowel movements a day, having to rush to the toilet to have a bowel movement, feeling of incomplete emptying after a bowel movement, and so on.…”
Section: Discussionsupporting
confidence: 64%
“…Comparison with functional diarrhea, respondents with IBS-D had even worse health-related quality of life. This may be due to that people with IBS-D had more frequent symptoms [6]. Further studies are required to explore the quality of life of functional diarrhea and its comparison with IBS-D.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was assessed through a validated questionnaire [14] and indicated as metabolic equivalents in hours per day. Anthropometric parameters were obtained in health centers by trained paramedical staff.…”
Section: Methodsmentioning
confidence: 99%
“…Irritable Bowel Syndrome (IBS) is the most prevalent dysfunction of gastrointestinal tract developed for unknown reasons and characterized by gastric pain in defecation and variations in bowel habits [1]. By the standard diagnostic criteria of IBS, its prevalence depends on numerous variables, but it has been reported as ranging 5-20% [2].…”
mentioning
confidence: 99%